2016
DOI: 10.5303/jkas.2016.49.6.295
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series Photometry of Variable Stars in the Globular Cluster NGC 288

Abstract: We present the results of BV time-series photometry of the globular cluster NGC 288. Observations were carried out to search for variable stars using the Korea Microlensing Telescope Network (KMTNet) 1.6-m telescopes and a 4k pre-science CCD camera during a test observation from August to December, 2014. We found a new SX Phe star and confirmed twelve previously known variable stars in NGC 288. For the semi-regular variable star V1, we newly determined a period of 37.3 days from light curves spanning 137 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We merged the SXP stars in these two catalogs, together with newly identified SXP stars in various globular clusters from recent work. These include NGC 288 (Martinazzi et al 2015a(Martinazzi et al , 2015bLee et al 2016) Furthermore, we rejected SXP stars with uncertain classification or membership, as well as those not a member of the globular clusters. The rejected SXP stars are: V83 in NGC 2419 (Clement 2017), SX8, SX17, and SX24 in NGC 5024 (Bramich et al 2012), BS19 in NGC 5053 (Arellano Ferro et al 2010), V25 in NGC 6093 (Clement 2017, V24 in NGC 6218 (Sariya et al 2018), V8, V9, V11, andV14 in NGC 6254 (Rozyczka et al 2018;Arellano Ferro et al 2020), V34 andV36 in NGC 6341 (Yepez et al 2020), V6 in NGC 6366 (Sariya & Yadav 2015), KT-05 in NGC 6656 (Rozyczka et al 2017), V11 in NGC 6779 (Clement 2017), and QU Sge in NGC 6838/M71 (McCormac et al 2014).…”
Section: Sample and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We merged the SXP stars in these two catalogs, together with newly identified SXP stars in various globular clusters from recent work. These include NGC 288 (Martinazzi et al 2015a(Martinazzi et al , 2015bLee et al 2016) Furthermore, we rejected SXP stars with uncertain classification or membership, as well as those not a member of the globular clusters. The rejected SXP stars are: V83 in NGC 2419 (Clement 2017), SX8, SX17, and SX24 in NGC 5024 (Bramich et al 2012), BS19 in NGC 5053 (Arellano Ferro et al 2010), V25 in NGC 6093 (Clement 2017, V24 in NGC 6218 (Sariya et al 2018), V8, V9, V11, andV14 in NGC 6254 (Rozyczka et al 2018;Arellano Ferro et al 2020), V34 andV36 in NGC 6341 (Yepez et al 2020), V6 in NGC 6366 (Sariya & Yadav 2015), KT-05 in NGC 6656 (Rozyczka et al 2017), V11 in NGC 6779 (Clement 2017), and QU Sge in NGC 6838/M71 (McCormac et al 2014).…”
Section: Sample and Datamentioning
confidence: 99%
“…This is because SXP stars also obey a period-luminosity (PL) relations similar to other classical pulsating stars. Examples of the empirical PL, or the period-luminosity-metallicity, relations for SXP stars can be found in Nemec & Mateo (1990), Nemec et al (1994), McNamara (1995), Pych et al (2001), Jeon et al (2003), Jeon et al (2004), Cohen & Sarajedini (2012), Fiorentino et al (2014), Kopacki (2015), Martinazzi et al (2015a), Martinazzi et al (2015b), and Lee et al (2016). Some derivations of the PL relations included both SXP and δ Scuti stars (Poretti et al 2008;McNamara 2011;Barac et al 2022), at which two recent works suggested the PL relation for δ Scuti stars could be broken (Gaia Collaboration et al 2022) or segmented (Martínez-Vázquez et al 2022).…”
mentioning
confidence: 99%
“…Similarly, CB that turned out not a member of the globular clusters or being re-classified as other types of variable stars were removed. These include: V2 in M12 (Kaluzny et al 2015); KT-01, KT-03, KT-15, KT-39, KT-40 & KT-41 in M22 (Rozyczka et al 2017); V27, V28 & V29 in NGC6712 (Deras et al 2020); V97 in M14 (Contreras Peña et al 2018); and V10 in NGC288 (Lee et al 2016). Therefore, our final list consists of 79 CB in 15 globular clusters.…”
Section: Selection Of Contact Binaries In Globular Clustersmentioning
confidence: 99%
“…The observations of J0247-25 were conducted for 9 nights from July 28 to October 4, 2014, at the second host site, SAAO, and for 14 nights from November 1 to 22, 2014, at the third site, SSO, during the telescope commissioning phase of each site. A 4k CCD camera with an image scale of 0.36 arcsec pixel −1 and a field of view of 25×25 arcmin 2 (Lee et al 2016) was used.…”
Section: Bv Photometry With Kmtnetmentioning
confidence: 99%